Pemetaan Bibliometrik Terhadap Penelitian dan Perkembangan Publikasi Dominating Graph - Dewi, Novian Riskiana (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to conduct bibliometric mapping of research and publication developments related to dominating graphs in the period from 2015 to 2024. The data was obtained through the google scholar database using Publish or Perish software with the keyword